2015
DOI: 10.12968/bjom.2015.23.6.388
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal screening and early-intervention: A mental health update from the NSPCC

Abstract: The NSPCC is dedicated to perinatal wellbeing and advocating for a preventative model of care that has the potential to improve the mental health for parents, families and communities. Here in the first of two articles, Camilla Sanger, Alice Haynes, Gary Mountain and Naomi Bonett-Healy provide an update of antenatal mental health research and recommended practice, with a specific focus on the role midwives can play in screening and identifying mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…More recently, in the implementation of home visiting programmes, there has been a shift towards more relationship based, psychotherapeutic approaches promoting parental reflectiveness and or mentalization through relationships in order to promote positive parenting, attachment and maternal sensitivity (Munro, 2011). T M ing the Baby® project commissioned by the National Society for the Prevention of Cruelty in Children (NSPCC) incorporates these types of approaches and is currently being piloted in the UK by the NSPCC (Sanger et al, 2015;NSPCC, 2015) having proven successful in the USA. This is an intensive, flexible, relationshipbased, interdisciplinary, trauma-informed and mentalization-based programme, embedded in community health care.…”
Section: Contemporary Approaches To Home Visiting Programmesmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, in the implementation of home visiting programmes, there has been a shift towards more relationship based, psychotherapeutic approaches promoting parental reflectiveness and or mentalization through relationships in order to promote positive parenting, attachment and maternal sensitivity (Munro, 2011). T M ing the Baby® project commissioned by the National Society for the Prevention of Cruelty in Children (NSPCC) incorporates these types of approaches and is currently being piloted in the UK by the NSPCC (Sanger et al, 2015;NSPCC, 2015) having proven successful in the USA. This is an intensive, flexible, relationshipbased, interdisciplinary, trauma-informed and mentalization-based programme, embedded in community health care.…”
Section: Contemporary Approaches To Home Visiting Programmesmentioning
confidence: 99%
“…This is in keeping with results from other studies with a meta-analysis by Brooten et al (2003) which concluded that a greater dose of advanced practice nursing services was associated with better patient outcomes as well as decreased health-care costs. D (GM) current experiences within a NSPCC funded international research project, the complexity of the work that is often involved in home visiting programmes necessitates the use of expert practitioners, often delivering complex interventions who in turn require intensive training and clinical supervision in order to acquire specific skills and developmental approaches for working with young mothers (Sanger et al, 2015). Questions still remain as to how best to meet the complex and substantial needs of populations of high risk young mothers and their children with frequent histories of complex trauma and adversity.…”
Section: Delivery Of Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Midwives are uniquely positioned to address the mental health needs of pregnant women due to the frequent contact expectant mothers will have with midwives, allowing a trusting relationship to be built (Madden et al, 2018; Sanger et al, 2015). However, working within a multidisciplinary team to include mental health services has been found to have better outcomes for women (Madden et al, 2018; Sanger et al, 2015). Despite the frequent contact pregnant women have with health professionals, identification of mental health problems is thought to be as low as 50% (NICE, 2014).…”
Section: Introductionmentioning
confidence: 99%